2022
DOI: 10.1155/2022/8280540
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation Analysis of Magnetic Resonance Imaging Characteristics and Prognosis of Invasive Pituitary Adenomas in Neurosurgery Hospitals

Abstract: The incidence of pituitary adenoma is second only to glioma and meningioma, and its incidence ranks third among intracranial tumors. Most pituitary adenomas are benign and noninvasive tumors, but invasive pituitary adenomas pose a great threat to human health. In order to explore the risk factors that affect the clinical aggressive behavior of patients with pituitary adenoma, analyze the correlation between different classification methods and clinical aggressive behavior, and lay the foundation for early judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The clinico-radiological risk factors comprised gender, age, tumor volume, Knosp grade (2 or 3), tumor diameter, hemorrhage (yes or no), suprasellar invasion (yes or no), periarterial enhancement (yes or no), and inferolateral venous compartment obliteration (yes or no). After statistical analysis, a nomogram was created to validate the test set [ 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinico-radiological risk factors comprised gender, age, tumor volume, Knosp grade (2 or 3), tumor diameter, hemorrhage (yes or no), suprasellar invasion (yes or no), periarterial enhancement (yes or no), and inferolateral venous compartment obliteration (yes or no). After statistical analysis, a nomogram was created to validate the test set [ 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%